miR-27a-5p—Abundant Small Extracellular Vesicles Derived From Epimedium-Preconditioned Bone Mesenchymal Stem Cells Stimulate Osteogenesis by Targeting Atg4B-Mediated Autophagy - Li, Xiaoyun; Chen, Rumeng; Li, Yunchuan; Wang, Panpan; Cui, Yan; Yang, Li; Zhu, Xiaofeng; Zhang, Ronghua (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis (OP) is a disease affecting the elderly and is characterized by incremental fractures and bone fragility. Small extracellular vesicles (sEVs) derived from mesenchymal stem cells have been demonstrated to possess potent regeneration potential. In this study, we evaluated the osteogenesis effects of sEVs derived from Epimedium-preconditioned bone mesenchymal stem cells (EPI-sEV) on osteoblasts and ovariectomized rats. The underline mechanism of EPI-sEV-induced osteogenesis was explored by RNA-sequencing and verified by transfection with the corresponding mimic and inhibitor. EPI-sEV stimulates osteogenic differentiation of osteoblasts, and moderates both bone mass and microstructure in ovariectomized rats. Sequencing identified a unique enrichment of a set of miRNAs in EPI-sEV. Overexpression or inhibition in vitro demonstrated that the osteogenesis–inducing potential was primarily attributed to miR-27a-5p, one of the most abundant miRNAs in the EPI-sEV fraction. Dual-luciferase reporter assays showed that miR-27a-5p promoted osteogenesis through direct suppression of Atg4B by targeting its 3’ untranslated region. Additional experiments showed that miR-27a-5p suppressed autophagy that was activated in OVX rats. Moreover, osteogenic differentiation was ablated by intervention with rapamycin in osteoblasts. These data report the regenerative potential of EPI-sEV to induce osteogenic differentiation of osteoblasts leading to bone formation. This process is achieved by delivering sEV-miR-27a-5p to target Atg4B for further autophagy stimulation.